Membangun karakter nasionalisme pada siswa melalui novel Lingkar Tanah Lingkar Air karangan Ahmad Tohari - Dewi Quraisyin, Switia; Sofia, Ummu; Ekowati, Sri Harini; Rafli, Zainal (Franconesia, 2023)
This study aims to describe the value of nationalism found in the novel Lingkar Tanah, Lingkar Air written by Ahmad Tohari which is able to build student character. This study analyzes 5 forms of nationalism values, namely the process of forming and growing the nation, sentiment or awareness of belonging to the nation, national language and symbolism, social and political movements for the sake of the nation, as well as national doctrine and ideology with novels and students as research objects. This research is a descriptive-qualitative type of research and collects data from existing objects, namely in the form of quotations of words, phrases or sentences contained in the novel, the data is then described through interpretive explanations based on the theory used in the research. Data analysis in this study is a data analysis technique from Miles and Huberman. From the research carried out, it can be seen first, the total number of forms of nationalism values found in the novel Lingkar Tanah Lingkar Air is 81 data. Second, the narration carried out by the characters in this novel explicitly proves that there is a value of nationalism that is deemed suitable to hide the value of nationalism. Third, learning literature which is more theoretical makes students bored and feel uninterested. Need to practice directly and have to be directly involved in understanding a student's literary work. Fourth, students really like playing roles in learning novels because they are fun and not boring. Students consider novels to be more interesting and the words easier to understand, besides that, novels are considered to provide knowledge and knowledge that students have not known before.